Albert Grundlingh, The Dynamics of Treason: Boer Collaboration in the South African War of 1899-1902 Protea Book House, Pretoria, 2006: Shifty Burghers ñ Hensoppers and Joiners in the Orange Free State and the Transvaal (Historia, 2021)
Almost thirty years ago, Albert Grundlingh, now Professor of History at the University of Stellenbosch, published his weighty MA dissertation in Afrikaans, entitled Die 'Hensoppers' en 'Joiners', an exhaustively researched, detailed and probing analysis of the experience of Boer collaboration with the British during the Anglo-Boer or South African War of 1899-1902. The dustjacket of that volume had a photograph of a very debonair-looking author. What a pity that the re-issue of the original Afrikaans text does not include a new picture for comparative historical interest. The appearance at last of this historiographically important text in good, plain English translation (by Bridget Theron) is to be lauded. Not only does it render an invaluable service to notoriously monolingual English-speaking scholars of the war. Beyond that, in more general terms, a classic work of originality and distinction should now find a more prominent place in any list of essential reading on the complex and contested terrain of white politics in pre-Union South Africa.